2004
DOI: 10.1901/jaba.2004.37-213
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Method of Thinning Reinforcer Delivery During Differential Reinforcement

Abstract: Differential reinforcement of alternative behavior (DRA) may result in rates of reinforcement that are impractical for caregivers to implement; therefore, recent research has examined methods for thinning reinforcer delivery during DRA. In this study, reinforcer delivery was thinned during DRA by restricting access to the participant's alternative response materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 5 publications
1
35
0
1
Order By: Relevance
“…Of the 19 studies that included schedule thinning, a total of 52 applications 1 of FCT with schedule thinning were described. Schedule arrangements employed in these studies included: (a) delay schedules, which involve introducing delays to reinforcement following the emission of the target communication response (e.g., Fisher et al, 1993); (b) chain schedules, which, in the case of escape-maintained problem behavior, involve increasing the number of demands that must be completed before requests for a break will be honored (also described as "demand fading" or "response chaining," e.g., Lalli, Casey, & Kates, 1995); (c) multiple schedules, wherein the duration of a signaled reinforcement component is progressively decreased while the duration of a signaled extinction component is increased (e.g., Hanley et al, 2001); response restriction, which involves restricting access to the communication response (or device) for progressively longer periods of time (Roane, Fisher, Sgro, Falcomata, & Pabico, 2004). The Table provides a summary of the published studies employing these four methods of schedule thinning following FCT and each is described below.…”
Section: Schedule Thinning Proceduresmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 19 studies that included schedule thinning, a total of 52 applications 1 of FCT with schedule thinning were described. Schedule arrangements employed in these studies included: (a) delay schedules, which involve introducing delays to reinforcement following the emission of the target communication response (e.g., Fisher et al, 1993); (b) chain schedules, which, in the case of escape-maintained problem behavior, involve increasing the number of demands that must be completed before requests for a break will be honored (also described as "demand fading" or "response chaining," e.g., Lalli, Casey, & Kates, 1995); (c) multiple schedules, wherein the duration of a signaled reinforcement component is progressively decreased while the duration of a signaled extinction component is increased (e.g., Hanley et al, 2001); response restriction, which involves restricting access to the communication response (or device) for progressively longer periods of time (Roane, Fisher, Sgro, Falcomata, & Pabico, 2004). The Table provides a summary of the published studies employing these four methods of schedule thinning following FCT and each is described below.…”
Section: Schedule Thinning Proceduresmentioning
confidence: 99%
“…Roane et al (2004) used a response restriction procedure with two children with autism and intellectual disabilities who engaged in aggressive behavior. In this study, functional analyses showed that aggression was maintained by positive reinforcement for both children (access to attention and preferred items, respectively).…”
Section: Response Restrictionmentioning
confidence: 99%
See 3 more Smart Citations